2015
DOI: 10.1097/md.0000000000001060
|View full text |Cite|
|
Sign up to set email alerts
|

Systematic Review and Meta-Analysis of Carotid Artery Stenting Versus Endarterectomy for Carotid Stenosis

Abstract: There are disparities among the results of meta-analyses under different circumstances of carotid artery stenting (CAS) versus endarterectomy (CEA) for carotid stenosis. This study aimed to assess the efficacies of CAS and CEA for carotid stenosis at 5-year intervals and worldwide.Comparative studies simultaneously reporting CAS and CEA for carotid stenosis with at least 10 patients in each group were identified by searching PubMed and Embase in accordance with preferred reporting items for systematic reviews … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
30
0
1

Year Published

2016
2016
2019
2019

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 43 publications
(33 citation statements)
references
References 64 publications
2
30
0
1
Order By: Relevance
“…The results of previous systematic reviews and meta-analyses of all patients (asymptomatic+symptomatic) are also consistent with our results. Zhang et al 44 found that patients randomized to CAS had higher risks of periprocedural stroke or death, restenosis at 1-year follow-up, periprocedural transient ischemic attack, and stroke or death at both 4-and 10-year follow-ups. Brahmanandam et al 45 and Liu et al 46 also found CEA to be superior to CAS for periprocedural stroke or death.…”
Section: Discussionmentioning
confidence: 99%
“…The results of previous systematic reviews and meta-analyses of all patients (asymptomatic+symptomatic) are also consistent with our results. Zhang et al 44 found that patients randomized to CAS had higher risks of periprocedural stroke or death, restenosis at 1-year follow-up, periprocedural transient ischemic attack, and stroke or death at both 4-and 10-year follow-ups. Brahmanandam et al 45 and Liu et al 46 also found CEA to be superior to CAS for periprocedural stroke or death.…”
Section: Discussionmentioning
confidence: 99%
“…Recent meta-analyses [26][27][28][29][30][31][32] , which included the latest large studies, seem to support the superiority of CEA over CAS in the periprocedural period whereas longterm results are inconclusive ( table 2 ). The meta-analysis [29] published in 2011 showed that CAS, when compared with CEA, was associated with an increased risk of periprocedural outcomes of death, MI or stroke except for cranial nerve injury and MI.…”
Section: Meta-analysis Of Randomized Trialsmentioning
confidence: 99%
“…A meta-analysis of Vincent et al [30] revealed that the higher cumulative incidence of stroke-related events throughout long-term follow-up was possibly caused by an increased risk during the periprocedural period. Interestingly, Zhang et al [32] systematically reviewed the data comparing CAS with CEA in the treatment of CS and pooled the data to analyze the results in different aspects. This study concluded that CEA is superior to CAS with regard to the stroke or death rate within 30 days, especially from 2006 to 2015, in North America and Europe.…”
Section: Meta-analysis Of Randomized Trialsmentioning
confidence: 99%
“…1 Carotid stenting has been trialled but current evidence supports carotid endarterectomy as the treatment of choice in these cases. 2 Timing of non-stroke-related surgery depends on the condition of the patient and the urgency of surgery; elective surgery should be deferred for at least 3 months. This time can be utilized to address co-morbid conditions pharmacologically or by lifestyle modification (e.g.…”
Section: Perioperative Issuesmentioning
confidence: 99%